2006
DOI: 10.1159/000090211
|View full text |Cite
|
Sign up to set email alerts
|

Thai Stroke Patient Caregivers: Who They Are and What They Need

Abstract: Background and Purposes: Primary informal caregivers play a significant role in providing care to stroke survivors after having been discharged from the hospital. Our aims were to describe the characteristics of Thai stroke caregivers and to explore their needs while providing care to their stroke relatives. Methods: Using open-ended questions, we individually interviewed 20 caregivers of stroke survivors to identify their characteristics and their own needs. Additional field notes were made during all intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
3
20
0
3
Order By: Relevance
“…With an aging population and an increasingly economistic society, loneliness is becoming a concern due to its negative impact on social welfare. 25 In the present study, our aim was to involve not only institutionalized elderly persons, but also those who remained in their own homes while attending day/community centers. The choice of these two groups of elderly persons (institutionalized and those living at home and attending day/community centers) was not made in order to establish a comparison, but to obtain a wider spectrum of opinions, for as Neto 22 says, loneliness is a sentiment that can be expressed by a person in any situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With an aging population and an increasingly economistic society, loneliness is becoming a concern due to its negative impact on social welfare. 25 In the present study, our aim was to involve not only institutionalized elderly persons, but also those who remained in their own homes while attending day/community centers. The choice of these two groups of elderly persons (institutionalized and those living at home and attending day/community centers) was not made in order to establish a comparison, but to obtain a wider spectrum of opinions, for as Neto 22 says, loneliness is a sentiment that can be expressed by a person in any situation.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported that females predominate in the provision of elderly care. 25,26 The reasons given by the respondents for the selection of the significant person varied, ranging from the person providing economic support to being their principal caregiver and/or emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention that Buddhism has a strong influence in Thai traditional medicine since the essence of the Buddha's teaching is to convey people to seek liberation from illness and fear of death (17). Thus, Thai Buddhism represented not only religious beliefs, but also a means of finding ways of relieving and curing some symptoms and diseases (18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Saat yang sama, caregiver menderita masalah akibat perawatan pasien antara lain terkait masalah fisik seperti kelelahan, keletihan, pusing, masalah tidur, nyeri, dan kelemahan (Jullamate, P., Azeredo, Z., & Subgranom, R., 2006;Pierce dkk., 2012) .…”
Section: Penelitian Yang Dilakukan Oleh Arksey Danunclassified